2013
DOI: 10.1515/bmt-2013-4414
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Blended Learning in Biomedical Engineering

Abstract: Blended learning represents a way in which to solve the problem of limited human resources at the universities and still maintain high standards in education of biomedical engineers. The e-learning system THERAGNOSOS for Biomedical Engineering students has been developed using the authoring tool IDEA 7 Professional. THERAGNOSOS allows implementation of blended learning -a combination of presence activities and e-learning. Introducing enhanced scenario with delayed feedback in exercises lead to improvement of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Due to the nature of Biomedical Engineering, presence activities such as laboratory exercises or specialized seminars are required. Blended learning mixes online learning with in-person activities to create a long-term platform for effective mentorship of Biomedical Engineering students (Kožuško et al, 2012;Marrhich et al, 2021). Biomedical Engineering students would be able to efficiently generate and share supportive educational materials and learning resources in an online learning environment that is both efficient and interesting for students.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of Biomedical Engineering, presence activities such as laboratory exercises or specialized seminars are required. Blended learning mixes online learning with in-person activities to create a long-term platform for effective mentorship of Biomedical Engineering students (Kožuško et al, 2012;Marrhich et al, 2021). Biomedical Engineering students would be able to efficiently generate and share supportive educational materials and learning resources in an online learning environment that is both efficient and interesting for students.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few comprehensive studies focusing specifically on the efficacy of blended-style classes in a biomedical engineering curriculum. Researchers utilizing a blended model in a Medical Terminology course found that students in the blended course performed better on exams than those in the traditional class [4]. A comprehensive implementation of biomedical engineering e-learning laboratories was implemented at the same university in the biomedical engineering curriculum but there is no formal analysis comparing this blended style to other educational modalities [5].…”
Section: Introductionmentioning
confidence: 99%